PANDANGAN HUKUM EKONOMI SYARIAH TERHADAP HARGA LELANG BARANG JAMINAN - Syarief, Arzalsyah (Al-Amwal : Journal of Islamic Economic Law, 2016)
:Â  In the perspective of Islamic Economics auction collateral, is permitted with a note using the pillars of purchase, the terms of buying and selling and general conditions of sale and purchase, ranging from notice to customers that the goods are used as collateral has passed the due time, notice the condition of goods such guarantees, tender preparation until the results of the auction the collateral. Then the auction price realized collateral and must fulfill the will of rapprochement agreement between the seller and the buyer. The auction fee charged to the buyer is not intended to raise the price, but for the interests of the State and the fund will be used as a tax. while in the process of being auctioned pledge collateral offered to customers who first did a deal with the official sanctioning body in this case sharia pawnshops